2019
DOI: 10.1016/j.stemcr.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Defects in Human Three-Dimensional Retinal Organoid Model of X-Linked Juvenile Retinoschisis

Abstract: SummaryX-linked juvenile retinoschisis (XLRS), linked to mutations in the RS1 gene, is a degenerative retinopathy with a retinal splitting phenotype. We generated human induced pluripotent stem cells (hiPSCs) from patients to study XLRS in a 3D retinal organoid in vitro differentiation system. This model recapitulates key features of XLRS including retinal splitting, defective retinoschisin production, outer-segment defects, abnormal paxillin turnover, and impaired ER-Golgi transportation. RS1 mutation also af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 44 publications
0
72
1
Order By: Relevance
“…Here, we have analyzed the disease phenotype and expression profile within a staging system, which is largely consistent with their findings. Based on the staging system, the RO disease models established to date have all been early-or mid-stage (Parfitt David et al, 2016;Shimada et al, 2017;Teotia et al, 2017;Buskin et al, 2018;Deng et al, 2018;Guo et al, 2019;Huang et al, 2019;Li et al, 2019;Quinn et al, 2019). For example, in a previous RPGR-RP model established in our lab (Deng et al, 2018), impaired gene expression was found as early as D90, and impaired photoreceptor morphology was observed at approximately D150.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have analyzed the disease phenotype and expression profile within a staging system, which is largely consistent with their findings. Based on the staging system, the RO disease models established to date have all been early-or mid-stage (Parfitt David et al, 2016;Shimada et al, 2017;Teotia et al, 2017;Buskin et al, 2018;Deng et al, 2018;Guo et al, 2019;Huang et al, 2019;Li et al, 2019;Quinn et al, 2019). For example, in a previous RPGR-RP model established in our lab (Deng et al, 2018), impaired gene expression was found as early as D90, and impaired photoreceptor morphology was observed at approximately D150.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genes encoding ciliary proteins, mutations in two genes related to structural integrity of the retina have been studied in organoid cultures. Organoids derived from iPSCs of a X‐linked retinoschisis patient with RS1 mutation recapitulated the retinal phenotype 48 . In organoids derived from patient with mutations in the CRB1 gene, the outer limiting membrane was disrupted with ectopic photoreceptor cell bodies detected beyond the apical limit of the neural retina 49 .…”
Section: Retinal Organoids As Disease Modelsmentioning
confidence: 94%
“…Most studies to date have used gene editing in iPSCs to rescue disease phenotypes 41,47,48 . However, such a strategy is not yet applicable for patient treatment.…”
Section: Evaluation Of Therapeutic Strategies In Human Retinal Organoidsmentioning
confidence: 99%
“…CRISPR-Cas-9 gene correction in retinal organoids has been tested successfully in several human RD models ( Deng et al, 2018 ; Huang et al, 2019 ; Lane et al, 2020 ) as well as in vivo in mice (with up to 45% efficiency of repair of dominant-negative Rho mutation to wild type allele in photoreceptors) ( Li et al, 2018 ). CRISPR-Cas-9-based repair may be especially productive and needed for RP diseases, which are caused by dominant-negative mutations, and may potentially work together with retinal tissue replacement (discussed above).…”
Section: D Retinal Tissue Models For Elucidating Disease Mechanisms mentioning
confidence: 99%